Effects of Omega-3 Fatty Acid Supplementation on Growth and Development of Bull Calves - Brandon J. Fraser; Allen G. Schwartz; Jason M. Warner (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective was to evaluate the supplementation of omega-3-based fatty acids to developing, post-weaned beef bull calves on growth and reproductive development. Study Description: This study was conducted over a 64-day period involving purebred Angus, Hereford, and Simmental bull calves (n = 42) born in spring 2023. The bulls were randomly assigned to three groups that included a control that did not receive the omega-3 supplement (n = 14) and calves that received 0.5 lb (n = 14) or 1.0 lb (n = 18) of the omega-3 supplement. The bulls were fed according to a ration formulated using the Growing Bull module of the Excel-based Beef Ration and Nutrition Decision Software (BRaNDS) formulation program. Results: No differences (P = 0.98) in initial body weight (BW) were observed among the treatment groups. Final BW for the 1.0 lb supplement group showed a trend toward higher values compared to the control; however, this was not significant (P = 0.77). Omega-3 supplementation increased (P = 0.04) average daily gain (ADG) in the 1.0 lb group with ADG values of 4.25 lb/day compared to 3.60 lb/day in the control group. The dry matter intake was consistent across groups (P = 0.64), indicating no effect of omega-3 supplementation on feed intake. However, the probability of passing the breeding soundness exam (BSE) was lower (P = 0.0097) in the 1.0 lb group, suggesting a negative impact on reproductive soundness. The Bottom Line: Omega-3 supplementation at 1.0 lb/day improved weight gain but had negative effects on reproductive soundness, lowering BSE pass rates.
Keywords: bulls; growth; fatty acid